The Effect of Sustainability Disclosure and Performance on The Accounting Performance of LQ45 Companies in Indonesia - Mutia Prawitasari; Noer Azam Achsani; Trias Andati (School of Business, Bogor Agricultural University (SB-IPB), 2026)
Background: Sustainability has emerged as a global priority, and in Indonesia, the issuance of POJK No. 51/2017 obliges all public companies to publish sustainability reports starting in 2020. Considering that prior studies have produced mixed findings regarding the relationship between sustainability and financial performance, this issue remains open for further empirical investigation.Purpose: This study aims to examine the effect of sustainability disclosure and sustainability performance covering economic, environmental, and social dimensions on the accounting performance of LQ45 companies during the mandatory sustainability reporting period.Design/methodology/approach: This quantitative empirical research analyzes 62 sustainability reports from 24 non-financial LQ45 companies over the period 2020–2022. Sustainability disclosure and sustainability performance are measured using content analysis based on the GRI Standards. Accounting performance is proxied by Return on Assets (ROA), and the hypotheses are tested using a fixed-effects panel regression model.Findings/Results: The results show an upward trend in both sustainability disclosure and sustainability performance over the observation period. Economic and environmental disclosures exhibit negative but statistically insignificant effects on accounting performance. In contrast, social disclosure shows a positive and significant effect, indicating that stakeholder-oriented practices such as employee welfare, product responsibility, and customer satisfaction contribute to improved accounting performance. Sustainability performance across all dimensions does not show a significant effect on accounting performance.Conclusion: Although economic and environmental disclosures may involve short-term costs, firms are encouraged to strengthen social disclosure, as it demonstrates a positive association with accounting performance.Originality/Value (State of art): This study integrates both sustainability disclosure and sustainability performance within the context of mandatory sustainability reporting. Keywords: sustainability disclosure, sustainability performance, accounting performance, financial performance, content analysis